The renaissance of muslim women: an identity of authentic islamic feminism in the Middle East (2005)
This study which employs both a textual and comparative approach seeks to explore the recent developments and conditions of Muslim women in some selected Middle Eastern countries. It traces the origins and development of Islamic feminism and seeks to understand the place and image of women portrayed by Islamic feminists as they contradict those of secular feminists and their feminist aspirations. The study reveals that though today, the Muslim woman has come to represent the ultimate symbol of oppression, a depiction that has been exacerbated by the mistaken belief in feminist discourse that the only true model of emancipation is the Western model; yet, there has arisen a growing elite of Muslim women who choose to reject this secular representation as alien to their perception of Islam. To these women who believe strongly in the egalitarian teachings of Islam, it is possible to re-establish gender empowerment and equity in today's Muslim societies as done by the Prophet and his early successors to match the vision of the Islam that is projected in the egalitarian teachings of Islam. This study then concludes that the feminist aspirations of these women, especially in respect of what they perceive as a destructive and overzealous implementation of the shari'ah law in Muslim societies, can be checked not by going outside Islam to establish gender justice, empowerment and freedom for women but by supporting the Islamic aspirations for the genuine emancipation and empowerment of women in all ramifications within only Islamic matrices